Factors affecting the price of raw milk in Turkey using panel data analysis - Mat, Burak; Arikan, Mehmet Saltuk; Cevrimli, Mustafa Bahadir; Akin, Ahmet Cumhur; Tekindal, Mustafa Agah (Univ Federal Santa Maria, 2021)
The high costs of feed among the total costs of raw milk production and an unfavorable milk-feed ratio directly affect the profitability of milk producers. To understand how the market in Turkey can be equilibrated, an exploration of the factors affecting milk prices is essential. This study determined the effects of the basic and the economic indicators on the price of raw milk between 2010 and 2019, by analyzing the monthly panel data. Since time series data are used, Augmented Dickey-Fuller (ADF) and Phillips-Perron (PP) tests are conducted to find out whether the series is stationary. In order to see the individual effects, the parameters are estimated using the fixed and random-effects models. The Hausman test is conducted to decide which of the two models is valid. The basic indicators for milk price, namely, prices of barley, soybean meal, wheat and distillers dried grains with soluble (DDGS). and the economic indicators. namely, dollar exchange rate and agricultural producer price index (PPI) had significant (P < 0.05: P < 0.01) effects on the milk price. In conclusion, it is reported that the raw milk prices in Turkey are considerably affected by the prices of feed ingredients as well as the general economic conditions.
Fatores que afetam o preço do leite cru na turquia usando análise de dados em painel
Keywords: economics; feed price; milk price; panel data; Turkey